Expanding the social cure: a mixed-methods approach exploring the role of online group dance as support for young people (aged 16–24) living with anxiety - Finn, Saoirse; Wright, Laura H. V.; Mak, Hei Wan; Åström, Emili; Nicholls, Lucy; Dingle, Genevieve A.; Warran, Katey (Frontiers in Psychology, 2023)
There is an increased interest in whether online arts interventions support mental health and social connections. This study explored eight weeks of online group dance as support for young people (aged 16–24) living with anxiety. The applicability of the ‘social cure’ theoretical framework to the novel context of an online dance class was sought. The study utilised an embedded QUAL+quan design, incorporating participatory focus group discussions (n = 3 groups; n = 11 participants) and one-on-one interviews (n = 2 participants), creative reflections (n = 16 participants) and ethnographic fieldnotes, and a repeated measures design with surveys at three timepoints (week 1, n = 27; week 4, n = 18; week 8, n = 14). Thematic analysis identified two overarching themes demonstrating how the dance classes (i) provided the opportunity to co-construct a meaningful shared identity and (ii) supported holistic wellbeing. The quantitative findings supported this, suggesting lower anxiety, depression, and loneliness and higher wellbeing, self-esteem, self-efficacy, and group closeness. This study expands the social cure to its application to an online dance context for the first time.